Repurposing Combination Therapy of Voacamine With Vincristine for Downregulation of Hypoxia-Inducible Factor-1α/Fatty Acid Synthase Co-axis and Prolyl Hydroxylase-2 Activation in ER+ Mammary Neoplasia - Singh, Lakhveer; Roy, Subhadeep; Kumar, Anurag; Rastogi, Shubham; Kumar, Dinesh; Ansari, Mohd. Nazam; Saeedan, Abdulaziz S.; Singh, Manjari; Kaithwas, Gaurav (Frontiers in Cell and Developmental Biology, 2021)
Abstract The current study was attempted to inquest the role of combination therapy of Voacamine and Vincristine for the prevention of mammary gland carcinoma through prolyl hydroxylase‐2 activation. The prolyl hydroxylase‐2 activation leads to the downregulation of hypoxia‐inducible factor‐1α and fatty acid synthase. Over expression of hypoxia inducible factor-1α and fatty acid synthase is previously reported in solid tumors of the mammary gland. Methods: After screening a battery of natural compounds which were similar to viG1ristine, Voacamine was selected as a possible prolyl hydroxylase‐2 activator and evaluated its activity using 7, 12-Dimethylbenz[a]anthracene induced rat model. The combination therapy was evaluated for cardiac toxicity using a hemodynamic profile. The angiogenic markers were evaluated using carmine staining. Monotherapy and combination therapy were also evaluated for liver and kidney toxicity through hematoxylin and eosin staining. The antioxidant potential delineated through oxidative stress markers. Serum metabolomics profile was studied with NMR spectroscopy and the disruption of fatty acids was evaluated using gas chromatography. Western blotting of proteins involved in hypoxic pathways was performed to decipher the action of therapy at the molecular level. Results: The immunoblotting analysis validated that combination therapy has the potential to switch on the prolyl hydroxylase‐2 activity and thus initiate proteolytic degradation of hypoxia‐inducible factor‐1α and its consequeG1e effects. The combination therapy also stimulated programmed cell death (apoptosis)in rapidly dividing cancer cells. Conclusion: The present study explores the role of voacamine in activation of prolyl hydroxylase‐2 which can decrease the overexpression of hypoxia‐inducible factor‐1α and fatty acid synthase in cells of mammary gland carcinoma.